Accuracy of Children's and Parents' Memory for a Novel Painful Experience - Melanie A Badali; Rebecca R Pillai; Kenneth D Craig; Kelly Giesbrecht; Christine T Chambers (Pain Research and Management)
BACKGROUND: Despite recent progress in understanding memory of pain in adults, the validity of the assumption that these findings extend to children has not been established. Because treatment often is evaluated on the basis of pain recall, it is crucial that the accuracy of pain memories in children be established.